2010
DOI: 10.1242/jeb.043356
|View full text |Cite
|
Sign up to set email alerts
|

Why do colder mothers produce larger eggs? An optimality approach

Abstract: SUMMARYOne of the more common patterns of offspring size variation is that mothers tend to produce larger offspring at lower temperatures. Whether such variation is adaptive remains unclear. Determining whether optimal offspring size differs between thermal environments provides a direct way of assessing the adaptive significance of temperature-driven variation in egg size. Here, we examined the relationship between offspring size and performance at three temperatures for several important fitness components i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 53 publications
2
70
2
Order By: Relevance
“…Huestis and Marshall, 2006;Mousseau and Dingle, 1991a;Mousseau and Dingle, 1991b;Mousseau and Fox, 1998b), offspring size and growth (e.g. Bacigalupe et al, 2007;Bownds et al, 2010;Chambers and Leggett, 1996;Fischer et al, 2003a;Fischer et al, 2003b;Fox et al, 1999;Kaplan and Phillips, 2006;Salinas and Munch, 2012), dispersal ability (e.g. Burgess and Marshall, 2011;Marshall, 2008) and developmental plasticity (e.g.…”
Section: Research Articlementioning
confidence: 99%
“…Huestis and Marshall, 2006;Mousseau and Dingle, 1991a;Mousseau and Dingle, 1991b;Mousseau and Fox, 1998b), offspring size and growth (e.g. Bacigalupe et al, 2007;Bownds et al, 2010;Chambers and Leggett, 1996;Fischer et al, 2003a;Fischer et al, 2003b;Fox et al, 1999;Kaplan and Phillips, 2006;Salinas and Munch, 2012), dispersal ability (e.g. Burgess and Marshall, 2011;Marshall, 2008) and developmental plasticity (e.g.…”
Section: Research Articlementioning
confidence: 99%
“…However, it has been observed that changes in egg size with ambient temperature may occur within a single generation, indicating the effect of phenotypic plasticity (Blanckenhorn, 2001). Despite a growing number of studies investigating the selective benefits of egg size at different temperatures (Blanckenhorn, 2000;Fischer et al, 2003;Bownds et al, 2010;Burgess and Marshall, 2011), to our knowledge, only one experiment has attempted to determine whether egg size and phenotypic plasticity for this trait can evolve (Azevedo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Across animals, experimental parental temperatures during egg production impact components of offspring fitness, often enhancing fitness in warmer compared with cooler parental temperatures (Gilchrist and Huey, 2001;Shine, 2006;Steigenga and Fischer, 2007;Lorioux et al, 2012; but see Rodríguez-Díaz and Braña, 2011;Guillaume et al, 2016). In several fish species, offspring growth at a given temperature is greatest when the parental temperature is the same (Bownds et al, 2010;Salinas and Munch, 2012;Shama, 2015). Moreover, the complexity of thermal non-genetic effects is becoming more apparent through evidence of persistence to the grand-offspring generation , discordant paternal and maternal effects Guilluame et al, 2016), and possible bet hedging of offspring phenotype (Shama, 2015).…”
Section: Introductionmentioning
confidence: 99%